1971
DOI: 10.1126/science.171.3970.480
|View full text |Cite
|
Sign up to set email alerts
|

Solifluction: A Model Experiment

Abstract: Laboratory experiments that subjected soil to repeated freeze-thaw cycles in an inclined container revealed every process of solifluction, especially of frost creep. Multiple slope-angle effects on the amount of particle movement on the soil surface in every cycle are interpreted by several characteristic processes of frost creep. Gelifluction was found to occur in thicker layers of soil, owing to the excess water retained in soil after thawing. For further development of the problem, a similarity law for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
2
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 1 publication
1
47
2
1
Order By: Relevance
“…The surface velocity is linearly correlated with the parameter Σ H tan 2 θ (Figure 11b), which may be explained by the experimental result that needle-ice creep is proportional to tan 2 θ (Higashi and Corte, 1971). In an earlier report, Matsuoka (1998a) derived an empirical relation, V S = 3·0 Σ H tan 2 θ, using data from Aino-1 and 3.…”
Section: Controls On Spatial Variabilitymentioning
confidence: 87%
“…The surface velocity is linearly correlated with the parameter Σ H tan 2 θ (Figure 11b), which may be explained by the experimental result that needle-ice creep is proportional to tan 2 θ (Higashi and Corte, 1971). In an earlier report, Matsuoka (1998a) derived an empirical relation, V S = 3·0 Σ H tan 2 θ, using data from Aino-1 and 3.…”
Section: Controls On Spatial Variabilitymentioning
confidence: 87%
“…Based on absolute t-values, slope angle is the second most important control of movement rates for all soil textures combined and for fine sections, and the most important control in stony and blocky areas. Field studies of clast transport by needle ice by Mackay and Mathews (1974) and Pérez (1987a), and laboratory studies by Higashi and Corté (1971), have shown that clast movement rates are dependent on slope gradients, with more rapid movement occurring on steeper slopes. In contrast, previous studies from the Subantarctic (Smith, 1960;Walton and Heilbronn, 1983;Selkirk, 1998) have failed to identify a clear relationship between slope angle and sediment movement rate.…”
Section: Discussionmentioning
confidence: 97%
“…From these three different models, that of Higashi and Corte (1971) best matches the 10 mm of downslope movement measured from the marker pen in the time lapse photographs. Matsuoka (1998) also found that Equation (2) best predicted downslope movement in his study on frost creep in the Japanese Alps.…”
Section: Short-term Observationsmentioning
confidence: 90%
“…This equation assumes that as the needle ice melts, the clast drops vertically to the surface. Through laboratory experiments, Higashi and Corte (1971) found that as the needle ice melted, clasts fell, rolled, and slid downslope instead of dropping vertically and settling. They formulated the equation:…”
Section: Short-term Observationsmentioning
confidence: 99%